2020
DOI: 10.3390/ani10010098
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of the Effects of Tylosin on the Composition and Metabolism of Canine Fecal Microbiota

Abstract: The present study investigated the in vitro effects of tylosin (TYL), alone or associated with prebiotics (PRE), on selected canine fecal parameters. Eight treatments were set up: control diet with no addition of substrates; TYL; Fructooligosaccharides (FOS); Galactooligosaccharides (GOS); Xylooligosaccharides (XOS); TYL + FOS; TYL + GOS; TYL + XOS. The flasks (five for treatment), containing a canine fecal suspension (prepared with the feces of healthy adult dogs) and the residue of an in vitro digested dry d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
1
7
0
1
Order By: Relevance
“…In one study, it was demonstrated that prednisone was as effective as a combined treatment with prednisone and metronidazole for induction therapy of canine IBD, putting the usefulness of metronidazole in treating CE in question [ 40 ]. The high relapse rate of dogs receiving antibiotics to treat CE can also be caused by an antibiotic-induced dysbiosis, as was reported for tylosin and metronidazole [ 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 92%
“…In one study, it was demonstrated that prednisone was as effective as a combined treatment with prednisone and metronidazole for induction therapy of canine IBD, putting the usefulness of metronidazole in treating CE in question [ 40 ]. The high relapse rate of dogs receiving antibiotics to treat CE can also be caused by an antibiotic-induced dysbiosis, as was reported for tylosin and metronidazole [ 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 92%
“…This is not unexpected when using an antibiotic, and this finding is consistent with other studies, albeit performed on healthy animals 10 , 12 or in vitro. 29 …”
Section: Discussionmentioning
confidence: 99%
“…The temperatures of the injector and detector were 200 °C, and the oven temperature was 155 °C. 2-ethylbutyric acid (Sigma Aldrich, Taufkirchen, Germany) was used as the internal standard [ 23 ]. The concentrations of ammonia and SCFA were determined in duplicate.…”
Section: Methodsmentioning
confidence: 99%
“…[ 27 ] were evaluated by qPCR using specific oligonucleotides ( Table S2 ). SYBR-based qPCR assays were performed following the run protocol described previously [ 23 , 28 ]. Each sample was run in duplicate while standard curves were run in triplicate.…”
Section: Methodsmentioning
confidence: 99%